Impact of weight loss on sexual and psychological functions and quality of life in females with sexual dysfunction: A forgotten avenue - Abdelsamea, Gehan A.; Amr, Mostafa; Tolba, Ahmed M. N.; Elboraie, Haitham O.; Soliman, Amir; Al-Amir Hassan, Badr; Ali, Faten; Osman, Doaa A. (Frontiers in Psychology, 2023)
Objectives This study aimed to evaluate the impact of weight loss on sexual and psychological health as well as quality of life in females with sexual dysfunction. Materials and methods The study was done at Delta University for Science and Technology in Gamasa, Egypt, on 40 obese married females having sexual dysfunction. Their age ranged from 20 to 40 years old, with a mean of 28.98 ± 4.96 years. They followed a weight loss program in the form of diet regimen and physical training for 6 months. Anthropometric measures, Arabic Female Sexual Function Index (FSFI), Arabic version of Hospital Anxiety and Depression Scale (HADS), and Arabic version of Short-Form 36 Health Survey (SF-36) were evaluated prior to starting the study, after 3 and 6 months of the study. Results Statistical analysis revealed significant reductions in anthropometric measures, as well as significant improvements in HADS and SF-36 scores after both 3 and 6 months of weight loss intervention compared to the baseline measurements, while there were significant improvements in sexual arousal, lubrication, patient satisfaction as well as the total score of FSFI after 3 months and contrarily there were no statistically significant changes in any of the FSFI’s domains or overall score after 6 months of the weight loss program compared to baseline. Conclusion Weight loss improves females’ anthropometric measures, psychological function and quality of life; however, it has no direct effect on female sexual dysfunction (FSD) after 6 months compared to baseline, so increased awareness of FSD is necessary as this issue suffers from inadequate identification and management.